2005
DOI: 10.1097/01.brs.0000153346.40391.3b
|View full text |Cite
|
Sign up to set email alerts
|

Orthoses for Mild Scoliosis: A Prospective Study Comparing Traditional Plaster Mold Manufacturing With Fast, Noncontact, 3-Dimensional Acquisition

Abstract: Based on our results, we believe that the computer-aided design procedure is equally efficient to traditional method for mild scoliotic curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…This, however, is a night-time sidebending brace, which requires fewer brace specifications than the typical full-time scoliosis brace. Cottolorda recently demonstrated that orthoses made through a CAD procedure compared favorably with those made through the classic procedure [9]. His brace is fabricated using a noncontact, three-dimensional optical scanner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, however, is a night-time sidebending brace, which requires fewer brace specifications than the typical full-time scoliosis brace. Cottolorda recently demonstrated that orthoses made through a CAD procedure compared favorably with those made through the classic procedure [9]. His brace is fabricated using a noncontact, three-dimensional optical scanner.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional scoliosis braces are typically crafted from customized casts or molds made of the patient's trunk, which requires significant physical contact. More recently, computer-aided design/computer-aided manufacture (CAD/CAM) has been introduced in scoliosis bracing design and manufacture to try to eliminate this plaster molding and decrease the subjective nature of different orthotists' skills and training [7][8][9]. Night-time braces have been described that use CAD for the modeling phase by Lemaire et al [7] and D'Amato et al [8], whereas Cottolorda et al [9] described a noncontact three-dimensional scanner for data acquisition with CAD software for modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The radiation exposure required for CT and high cost of MRI preclude the use of these imaging techniques merely for purposes of clinical evaluation. We are working on noninvasive optical measurement methods for objectively assessing the degree of correction [12].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, this technology has been applied to asymmetrical scoliosis bracing design and manufacture (Cottolorda et al, 2005;D'Amato, Griggs, and McCoy, 2001;Lemaire, Goudreau, and Jeffreys, 1996). While CAD by itself provides accurate, reproducible modeling, it is how-ever significantly impacted by the accuracy of the data acquisition system and the quality of the templates.…”
Section: Modelingmentioning
confidence: 97%